PERKEMBANGAN KESENIAN JARAN JENGGO ASWO KALOKO JOYO GENERASI KE-6 SAMPAI GENERASI KE-7 DESA SOLOKURO KECAMATAN SOLOKURO KABUPATEN LAMONGAN (Indonesian Journal of Conservation, 2018)
Jaran Jenggo art is a circumcision dress art procession using a horse or jaran accompanied by jedor music. Jaran Jenggo art began to develop from the 6th generation to the 7th generation which has been implemented because of various aspects of modern thought, education and economics Making Jaran Jenggo Art Aswo Kaloko Joyo makes art form innovation so that it is not monotonous. It is this change that motivates. Jaran Jenggo Aswo Kaloko Joyo developed the form. The aim of the study was to find out the development. Jaran Jenggo Aswo Art Kaloko Joyo from the 6th generation to the 7th day. This study uses qualitative methods through the Sociology of Arts approach to encode the development of society towards artists in the creation of films. Jaran Jenggo to make it look more attractive. Social change, making Jaran Jenggo Art finally began to rise with innovative forms, accompaniment, costumes and make-up, even to the stage that consisted of the farewell stage which began in the 6th Generation to become a new form and developed until the 7th generation ofization. Jaran Jenggo Art Aswo Kaloko Joyo has found a country that is mature enough in the mood, with the development that creates Jaran Jenggo still has to improve the quality and quality of the art they have.